Internal Control and Financial Reporting Quality in Banking: A Conceptual Synthesis - Erik Kartiko; Mochamad Romdhon (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Internal control over financial reporting plays a critical role in determining the overall quality of financial statements, especially in banks under high regulatory pressure and using forward-looking accounting standards and complex financial instruments like IFRS 9. Despite a voluminous literature on the subject, concepts of internal control mechanisms remain fragmented and lack conceptual integration in relation to financial reporting outcomes. Objective: This study aims to explore internal control over financial reporting as a tool to improve the quality of financial reports in the banking sector and to provide an integrated conceptual framework on the relationship between governance mechanisms, effectiveness of internal control and reporting quality. Methods: The study uses a structured analytical approach based on a structured empirical literature synthesis. This research explores the banking context by reviewing and integrating 13 relevant empirical studies exploring the interaction between governance structures, internal control systems, and indicators of financial reporting quality. Results: The outcomes suggest that efficient internal control systems substantially increase financial reporting quality through reduced opportunistic behavior, improved transparency, and intensified adherence to accounting standards.  Audit committees and board independence, as governance mechanisms, strengthen the effectiveness of internal controls. Conclusion: The results of the study reveal that internal control over financial reporting and governance mechanisms are complementary solutions that jointly lead to superior quality of financial reporting, thus forming a cohesive model to ensure transparency and accountability in the banking sector.